The fermocrat strategy: expanding the repertoire of feminist activists - Chappel, Louise (2002)
The parliamentary arena has presented many obstacles to those wanting to use this arena to improve women's representation. It has become increasingly obvious that to make governments sore sensitive to women and to gender issues, feminists need to engage with multiple institutions simultaneously. Australian feminists have had made some advances exploiting opportunities in the bureaucracy. However, this successful `femocrat' strategy has not been replicated in either Canada or the UK - two similar Westminister systems. The article explores the reasons for these differences and argues that they are the result of variations in the political opportunity structure. Three features are considered: bureaucratic norms, political parties and federalism. Although to date UK feminists have had the least favourable Political Opportunity Structure in relation to the public service and public administration, signs are emerging that this is changing and that in future, they may be able to expand their repertoire in this direction. - Reproduced.
Keywords: Women in politics